Forced Convection Around a Solid Cylinder - MOHD YUSOFF, NUR AZIZI HILMAN; KAMARDAN, MUHAMAD GHAZALI (Enhanced Knowledge in Sciences and Technology, 2025)
Forced convection heat transfer is essential in engineering applications,offering insights into optimizing thermal systems for efficiency andreliability. This study focuses on analysing forced convection around asolid cylinder using COMSOL Multiphysics software. Dimensionalequations were transformed into dimensionless forms to facilitatesimulation. Results revealed significant changes in streamline andvelocity patterns as Reynolds numbers varied (Re = 1, 10, 20, 40),demonstrating the transition from laminar to complex flow dynamicsand its impact on heat transfer. This work highlights the potential ofCOMSOL Multiphysics for studying thermal phenomena and proposesfurther research on complex geometries and varied parameters.